Comparison of the economic efficiency and sustainability of two debonding processes for structurally bonded sills - Alex Jordan; Lucas Hermelingmeier; Julian Gilich; Gerson Meschut; Marco De Santis; Alexander Schlüter (Journal of Advanced Joining Processes, 2025)
In light of growing demands for resource efficiency and sustainability in vehicle engineering, the environmentally compatible separation of structural adhesive joints is gaining increasing relevance. This study presents a comparative analysis of two physically based debonding methods: the established hot-air process and a cryogenic cold process based on liquid nitrogen (LN2). The primary objective is to assess the ecological impact and process-related sustainability of both approaches.Experimental investigations were conducted on a component-representative triple-sheet structure that simulates common automotive flange joints. Thermal input was applied either by convective heating using a hot air gun or by direct cooling through a contact-based LN2 tool. The resulting temperature profiles were recorded using spatially distributed thermocouples. Subsequently, the outer panel was selectively debonded to replicate a repair scenario, and the mechanical integrity of the remaining adhesive joint was evaluated through Mode I testing of l-shaped specimens. Process data served as input for an Life Cycle Assessment (LCA) according to DIN EN ISO 14,040.The cryogenic method achieved a 40 % reduction in carbon footprint compared to the hot-air process (0.337 kg vs. 0.559 kg CO2-equivalents), primarily due to its shorter process time and more efficient heat transfer. While the hot-air method’s impact is mainly driven by electrical energy use, that of the cold method stems from cryogenic media consumption. Notwithstanding certain disadvantages in specific impact categories, the LN2-based process exhibits a superior overall ecological performance and signifies a promising solution for repair- and recycling-oriented adhesive separation in structural vehicle applications.